New winter crops and rotations for the Pacific Northwest low‐precipitation drylands. (3rd September 2020) - Schillinger, William F.
Abstract: This article is an overview of recent advances in dryland cropping in the region of the Inland Pacific Northwest of the United States (PNW) that receives <300 mm annual precipitation. The climate of the region is Mediterranean‐like with wet winters and dry summers. For the past 130 yr, monocrop 2‐yr winter wheat ( Triticum aestivum L.)–fallow (WW–F) has been the dominant rotation practiced on >90% of rainfed cropland throughout this region. Rapid advances in technology in the past several decades and the realities of dryland farm economics prompted most farmers to expand their land area and adopt conservation tillage and no‐tillage practices. Three relatively new crops have gained some foothold in the past decade. These crops are winter pea (WP) ( Pisum sativum L.), winter canola (WC) ( Brassica napus L.), and winter triticale (WT) ( X Triticosecale Wittmack ). Like WW, all three of these "new" winter crops need to be planted in late August–early September into carryover soil moisture after a 13‐ to 14‐mo fallow period to achieve optimum yield potential. Researchers and farmers have experimented with a multitude of spring‐planted crops but, to date, all have shown high year‐to‐year variability in yield and none have been economically viable in the long term. The focus of this paper is to summarize major research conducted on WP, WC, and WT, as well as farmers' attitudes on the potential of these three winter crops for wheat‐based rotations in the PNW drylands.